Self-statements of medical students about the fear of speaking in public - Rosa Rossi-Barbosa, Luiza Augusta; Alves Carvalho Laube , Kaito; Camargo , José Fernando; Prates Caldeira , Antônio; Rossi Barbosa-Medeiros , Mirna (Bionorte, 2023)
Objective: to evaluate the perception of medical students from two institutions in the north of Minas Gerais regarding the fear of public speaking and the association with sociodemographic, economic and anxiety level variables. Materials and Methods: cross-sectional, analytical study, consisting of 346 students using identification data, Self-Statements during Public Speaking Scale (SSPS) and Beck Anxiety Inventory. Results: the mean age was 22.36 years with a predominance of females. The total SSPS score was 17.72 for the positive rating subscale and 5.28 for the negative subscale. Academics over 22 years old, with more than six minimum wages and with minimal to mild anxiety had a higher average on the positive subscale and those aged up to 22 years, less than six minimum wages, with moderate to severe anxiety and those in the initial periods had a higher average on the negative subscale. The practice of public speaking carried out in the first period was evaluated as positive. Conclusion: the variables age, income and level of anxiety were statistically significant for the positive and negative subscales of fear of public speaking, and academics in the initial periods of the course were significant for the negative subscale.